PENGARUH DEBT TO ASSET RATIO, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR HEAVY CONSTRUCTIONS AND CIVIL ENGINEERING YANG TERDAFTAR DI BEI - Vina Pramudita; Nisfu Fhitri (Smart Education, 2026)
Abstract: This study was conducted to determine whether there is an influence of Debt to Asset Ratio (DAR), Current Ratio (CR), and Debt to Equity Ratio (DER) on Return on Assets in Heavy Constructions and Civil Engineering Sub-Sector Companies Listed on the IDX. The population in this study is Heavy Constructions and Civil Engineering Sub-Sector Companies Listed on the IDX. The sample was taken using purposive sampling, so that 8 observations were obtained as samples. And using multiple linear regression methods, classical assumption tests, simultaneous tests (F tests) and partial tests (t tests). The results of this study indicate that Debt To Asset Ratio (DAR), Current Ratio (CR), and Debt To Equity Ratio (DER) simultaneously do not affect Return On Asset (ROA) obtained F count F table value (1.520 <2.95). The partial test results of the DAR, CR, and DER variables do not affect ROA because the significant value of DAR is 0.385>0.05 and t count (0.883) <t table (2.04523). The CR variable partially has a significance of 0.283>0.05 with a t count value (1.094) <t table (2.04523). The DER variable partially has a significance of 0.236>0.05 with a value of -thitung (-1.212) <-t tabel (-2.04523). The Adjusted R Square value or coefficient of determination is 0.048. This means that 4.8% of the variation or change in Return On Asset is explained by variations in Debt To Asset Ratio, Current Ratio and Debt To Equity Ratio 95.2% is influenced by other variables outside the research model. Keywords: Debt To Asset Ratio, Current Ratio, Debt To Equity Ratio dan Return On Asset Abstrak: Penelitian ini dilakukan untuk mengetahui apakah ada Pengaruh Debt To Asset Ratio (DAR),Current Ratio (CR), Dan Debt To Equity Ratio (DER) Terhadap Return On Asset Pada Perusahaan Sub Sektor Heavy Constructions And Civil Engginering Yang Terdaftar Di BEI. Populasi dalam penelitian ini adalah Perusahaan Sub Sektor Heavy Constructions And Civil Engginering Yang Terdaftar Di BEI. Sampel yang diambil dengan menggunakan purposive Sampling,sehingga diperoleh 8 pengamatan sebagai sampel. Dan menggunakan metode regresi linier berganda,uji asumsi klasik,uji simultan (uji F) dan uji parsial (uji t). Hasil penelitian ini menunjukan bahwa Debt To Asset Ratio(DAR),Current Ratio(CR),dan Debt To Equity Ratio(DER) secara simultan tidak berpengaruh terhadap Return On Asset (ROA) diperoleh nilai Fhitung<Ftabel(1,520<2,95).Hasil uji parsial variabel DAR,CR,dan DER tidak berpengaruh terhadap ROA karena nilai signifikan DAR sebesar 0,385>0,05 dan thitung(0,883)<ttabel(2,04523).Variabel CR secara parsial memiliki signifikan sebesar 0,283>0,05 dengan nilai thitung(1,094)<ttabel(2,04523).Variabel DER secara parsial memiliki signifikan sebesar 0,236>0,05 dengan nilai -thitung(-1,212)<-ttabel(-2,04523).Nilai Adjusted R Square atau koefisien determinasi adalah 0,048.hal ini berarti 4,8% variasi atau perubahan dalam Return On Asset dijelaskan oleh variasi Debt To Asset Ratio,Current Ratio,dan Debt To Equity Ratio 95,2%dipengaruhi oleh variabel-variabel lain diluar model penelitian. Kata Kunci: Debt To Asset Ratio,Current Ratio,Debt To Equity Ratio dan Return On Asset